The Sociological Approach to Islamic Da’wah Pendekatan Sosiologikal Dakwah Islam - Farooqui, Jamil (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
Abstract Da‘wah has been studied from different angles and from different points of view. The present paper deals with the sociological approach to da‘wah. It focuses on three aspects of da‘wah which has wide repercussions and a determinant impact on social relations and the lives of individuals. First, the significance of da‘wah from the sociological perspective is the nature of intellectual interaction where there is an exchange of ideas and ideals affecting the mind-set of individuals. Second, it is a vital form of social transformation which takes place at the intellectual level and proceeds to the physical level. Third, it has a distinct method based on the communicator, content, recipient and the style of communication. Keywords:Islamic Da‘wah, Intellectual Interaction, Social Transformation, Communication Process, Ideals. ******************************************* Abstrak Dakwah telah dikaji dari sudut pandangan yang berbeza. Karya ini berurusan dengan pendekatan sosiologikal untuk dakwah. Ia menumpukan perhatian kepada tiga aspek dakwah yang mempunyai pelbagai akibat dan kesan penentu kepada hubungan sosial dan kehidupan individu. Yang pertama, kepentingan dakwah dari perspektif sosiologikal adalah sifat interaksi secara intelektual dimana berlakunya pertukaran idea dan cita-cita yang mempengaruhi minda seorang individu. Kedua, ia adalah satu bentuk transformasi sosial penting yang berlaku pada tahap intelektual sehingga tahap fizikal. Ketiga, ia mempunyai kaedah yang berbeza berdasarkan komunikator, kandungan, penerima dan gaya komunikasinya. Kata Kunci: Dakwah Islam, Interaksi secara intelektual, Transformasi Sosial, Proses Komunikasi, Cita-cita.